Routledge handbook of revolutionary China - Baumler, Alan (Routledge, 2019)
Cover; Half Title; Title; Copyright; Contents; List of figures; List of tables; List of contributors; Introduction; 1 Japanese goals, Chinese realities at the grassroots: the Japanese Occupation in northern Zhejiang, 1937-42; 2 The rise of the Chinese Communist military-fiscal party-state in Shandong Province, 1937-45; 3 New China Daily: social change and the class project in wartime Nationalist China; 4 Liberation: a view from the Southwest; 5 The search for a Socialist everyday: the urban communes; 6 Changes in the rural land system and power structure in the countryside
Keywords: China -- History -- 1949-1976; China -- History -- Republic, 1912-1949; Electronic books